Post-COVID Insurance Purchase Intention: The Roles of Referral, Agent Characteristics, Influencer Credibility, Plan Value, and Trust - Kristabel, Agatha Jane; Wijaya, Serli; Jaolis, Ferry (Organizations and Markets in Emerging Economies, 2024)
The COVID-19 pandemic has heightened public awareness regarding the importance of health insurance. Several factors influencing the choice of an insurance brand include the plan value, agent characteristics, referrals, and consumer trust. Over the past five years, the use of influencers has expanded as they are believed to influence consumer intentions to purchase insurance services. Primary data was collected through a survey of 181 respondents who did not have an insurance policy but had seen the content of the insurance company’s marketing communications presented by influencers. Using SEM-PLS to analyze the primary data, the study found that agent characteristics and influencer credibility directly affect an insurance brand’s consumer trust and purchase intention. Meanwhile, referrals have a significant direct effect on consumer trust but not directly on purchase intention. Conversely, the plan value offered by insurance companies directly affects purchase intention but has no direct influence on consumer trust. Despite finding that consumer trust was insignificant in mediating the effect of referrals, agent characteristics, plan values, and influencer credibility on purchase intention, this study validates the role of agent characteristics, plan values, and influencer credibility in influencing consumer’s intention to purchase insurance products.
Keywords: Agent Characteristics; Insurance Purchase Intention; Influencer Credibility; Plan Value; Consumer Trust; Referral